ANALISIS TATA KELOLA PADA SISTEM INFORMASI LELANG MENGGUNAKAN FRAMEWORK COBIT 2019 MENGACU PADA DOMAIN EDM05 DAN BAI09 (STUDI KASUS : KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG CIREBON) - Sity Salimah; Muhammad Hatta; Willy Eka Septian (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2024)
Online auction website is one form of utilization of information technology provided by auction platforms in Indonesia to facilitate the auction process digitally, including the management of asset data, bids, and transactions. Management of auction information systems that are not managed properly can have an impact on the low quality of service, which in turn can affect the level of trust of users and stakeholders in the platform. Therefore, an Analysis of Information Technology Governance in the Auction Information System Using the COBIT 2019 Framework is needed to ensure that IT management is carried out effectively and efficiently in accordance with established standards. The purpose of this study is to improve the auction website system. This study uses a descriptive approach method. This study involved 86 participants. COBIT 2019 was chosen as the reference model in evaluating IT governance. The data collection technique used was a questionnaire.